2010
DOI: 10.4997/jrcpe.2010.205
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in out-of-hours emergency medical admissions – more than just a weekend effect

Abstract: Mortality among emergency medical admissions to hospital is higher for admissions at the weekend than on weekdays; this also holds true for certain specific conditions. However, it is unknown whether that effect is limited to weekends. This study calculated mortality in emergency medical admissions for each day of the week, and compared mortality at weekends with weekdays, at nights with days, and in all out-of-hours periods with in-hours in a UK district general hospital. Total mortality was increased for adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 22 publications
2
32
2
Order By: Relevance
“…Our ability to investigate the effect of test results, admission time, and hospital workload are major strengths of this study. Previous studies have considered overnight versus daytime, or shift patterns in small studies, 22 in specific conditions, 23 or did not adjust for illness severity 10 . We analysed data from unselected emergency admissions, avoiding potential coding bias by restricting our analysis to specific subgroups 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Our ability to investigate the effect of test results, admission time, and hospital workload are major strengths of this study. Previous studies have considered overnight versus daytime, or shift patterns in small studies, 22 in specific conditions, 23 or did not adjust for illness severity 10 . We analysed data from unselected emergency admissions, avoiding potential coding bias by restricting our analysis to specific subgroups 24 .…”
Section: Discussionmentioning
confidence: 99%
“…4 9 19 20 It was consistent with a previous in-hospital mortality report of 7.96% among 15 594 emergency medical admissions to a single centre. 8 Examinations of unscheduled activity across multiple acute hospital trusts in England have reported an overall crude mortality rate of 5.0% 1 and an adjusted case fatality rate of 4.3% (range 2.5-6.4%). 6 However, these inpatient population studies included groups in the denominator which could have a lower short-term risk of death such as hospital transfers and direct ward admissions from primary care, and did not count deaths occurring in the community after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the delivery of care in hospital during weekend hours due to reduced overall staffing levels, less senior and less experienced staff, and less supervision have all been quoted as possible explanations for the higher mortality which is called as 'weekend effect'. [6] The same reasons can be applied for higher mortality during holidays and night time. In addition, studies have shown that sleep deprivation of physicians is associated with a decline in performance [7,8], which may be a reason for higher mortality at night.…”
Section: Discussionmentioning
confidence: 99%